2022
DOI: 10.1039/d1cp04248c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxygen vacancies on the photoexcited carrier lifetime in rutile TiO2

Abstract: The photoexcited carrier lifetime in semiconductors plays a crucial role in the solar energy conversion processes. The defects or impurities in semiconductors are usually proposed to introduce electron-hole (e-h) recombination...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 87 publications
(144 reference statements)
0
9
0
Order By: Relevance
“…The e–h nonradiative recombination times were obtained by fitting the charge population using the exponential decay function f ( t ) = exp ( t τ ) 1 t / τ . This method has been widely used to study photoexcited carrier dynamics in various systems. In this calculation, the spin–orbit coupling (SOC) effects on the structural relaxation have not been included to reduce the computational effort because it has been proven that the results of SOC on charge distribution are rather limited …”
Section: Methodsmentioning
confidence: 99%
“…The e–h nonradiative recombination times were obtained by fitting the charge population using the exponential decay function f ( t ) = exp ( t τ ) 1 t / τ . This method has been widely used to study photoexcited carrier dynamics in various systems. In this calculation, the spin–orbit coupling (SOC) effects on the structural relaxation have not been included to reduce the computational effort because it has been proven that the results of SOC on charge distribution are rather limited …”
Section: Methodsmentioning
confidence: 99%
“…18 As indicated by NAMD, whether impurity energy levels serve as a recombination center is closely related to the nonadiabatic coupling strength coefficient; 19 which is proportional to electron−phonon scattering and the velocity of nuclear, and inversely proportional to the energy level difference. 20 For instance, the formed defect phonon scattering in black phosphorus is not favorable for fast electron−hole recombination. 21 Furthermore, shallow or deep energy defect levels in methylammonium lead halide perovskites do not enhance the carrier recombination because of their intrinsic weak bulk moduli and nonadiabatic coupling strengths.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent ab initio nonadiabatic molecular dynamics (NAMD) results reveal that the formed impurity energy levels in some compounds do not accelerate the recombination of photogenerated electrons and holes, and the classic Shockley–Read–Hall model fails . As indicated by NAMD, whether impurity energy levels serve as a recombination center is closely related to the nonadiabatic coupling strength coefficient; which is proportional to electron–phonon scattering and the velocity of nuclear, and inversely proportional to the energy level difference . For instance, the formed defect phonon scattering in black phosphorus is not favorable for fast electron–hole recombination .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, unravelling the role of V o with different characteristics in nonradiative recombination is critical for improving photocatalytic efficiency. Previous first-principles studies confirmed that single V o on the TiO 2 (110) surface serves as an effective SRH recombination center by introducing the deep polaronic in-gap states . However, the structure model is too simple to capture realistic conditions.…”
mentioning
confidence: 99%
“…Previous first-principles studies confirmed that single V o on the TiO 2 (110) surface serves as an effective SRH recombination center by introducing the deep polaronic in-gap states. 28 However, the structure model is too simple to capture realistic conditions. Theoretical prediction contradicts the quantitative experimental measurements, which show that the photocarrier lifetime is prolonged instead on the TiO 2 (110) surface with a higher concentration of V o .…”
mentioning
confidence: 99%